Legal Aspects of Biomedical Experiments on Humans in Russia - ZAKHARTSEV, Sergey I.; SALNIKOV, Viktor P. (Journal of Advanced Research in Law and Economics, 2019)
The relevance of the study is determined by the fact that it is often a question of diversification of possible restrictions that become the basis of antagonism between the scientific progress and the desire of human beings to preserve themselves. Therefore, such fragments are often unpredictable, since the question of the admissibility of conducting research on humans has always been part of the general social and philosophical system that determines the development of society. The novelty of the study is that for the first time in the legal and philosophical literature the question of the conformity of what is called biological and medical ethics is raised in accordance with the national culture and national identity. The authors of the article clearly identify the inseparability of the connection between the cultural and statistical approach to the expediency of regulating biomedical experiments and their legal regulation. The structure of international legislation and its regional adaptation in Russian legislation are revealed. The practical significance of the study is determined by the possibility of forming a stable position regarding the possibilities of expanding the subject of legal regulation of biomedical ethics. Results: ‎ The authors of the article determine that this is necessary for the complete improvement of the processes of socio-economic development, structural coordination of efforts aimed at achieving certain parameters and formation of a general picture regarding the holistic development of the ethical complex of a human being.